A Jacobi Waveform Relaxation Method for ODEs - Sand, J.; Burrage, K. (SIAM journal on scientific computing, 1998)
A Jacobi waveform relaxation (WR) method for solving initial value problems for ordinary differential equations (ODEs) is presented. In each window the method uses a technique called dynamic fitting and a pair of continuous Runge--Kutta (RK) formulas to produce the initial waveform, after which a fixed number of waveform iterates are computed. The reliability and efficacy of the method are demonstrated numerically by applying it to qualitatively different problems for linear tridiagonal ODEs.